The Influence Of E-Marketing Mix on Consumer Purchasing Decisions of E-Commerce Users - Shella Nabila; Hamid Halin; Shafiera Lazuarni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine whether there is an effect of E-Marketing Mix on Purchase Decisions in E-Commerce (Shopee, Tokopedia, and Lazada). This research is a descriptive quantitative research. There were 433 samples in the study using the slovin formula. The sample technique in this study used a purposive sampling technique. This research method uses multiple linear regression analysis with the help of the Statistical Product and Service Solution (SPSS) computer program version 24. Based on the research data the results of the multiple linear regression coefficient test obtained the final equation, namely Y = 1.490 + 0.563X1+ 0.279X2 +0.708X3+ 0.615X4 +0.018X5 +0.134X6 +0.798 X7 + e. Based on the results of the t test or partially where Product (X1) with a significant value of 0.000 <0.05 Price (X2) with a significant value of 0.000 <0.05 Place (X3) with a significant value of 0.000 <0.05 Promotion (X4) Process ( X5) with a significant value of 0.000 <0.05 with a significant value of 0.000 <0.05 People (X6) with a significant value of 0.000 <0.05 Physical Evidence (X7) with a significant value of 0.000 <0.05, which means that it can be said that the variable independent significant effect on the dependent variable. the variables studied have an influence on purchasing decisions. the results of the F test can be said to be 0.000 <0.05, which means Ho.